A single species of mangrove monitor (Varanus) occupies Ambon, Seram, Buru and Saparua, Moluccas, Indonesia - Valter Weijola; Samuel S. Sweet (AMPHIBIAN & REPTILE CONSERVATION, 2022)
According to current literature the islands of the central Moluccan region harbor at least three species of monitor lizards. This suggests similar patterns of species richness to the northern Moluccas and could imply significant taxonomic and ecological complexity throughout the Moluccan region. Field investigations in habitats from sea level up to 300 m elevation failed to locate more than one widespread species, by definition referable to Varanus indicus (type locality Ambon). Reassessments of records for other species of mangrove monitors show that these can either be attributed to taxonomic mis-identifications or to colonial-era specimens lacking reliable collection data. We test Principal Components Analysis of scalation characters as a diagnostic tool for some of the island populations and species within the Varanus indicus group.